Predictors of postnatal depression in the slums Nairobi, Kenya: a cross-sectional study - Esther W. Kariuki; Mary W. Kuria; Fredrick N. Were; David M. Ndetei (BMC Psychiatry, 2022)
Abstract Background Postnatal depression (PND) is a universal mental health problem that prevents mothers’ optimal existence and mothering. Although research has shown high PND prevalence rates in Africa, including Kenya, little research has been conducted to determine the contributing factors, especially in low-resource communities. Objective This study aimed to investigate the PND risk factors among mothers attending Lang’ata and Riruta Maternal and Child Health Clinics (MCH) in the slums, Nairobi. Methods This study was cross-sectional. It is part of a large study that investigated the effectiveness of a brief psychoeducational intervention on PND. Postnatal mothers (567) of 6-10 weeks postanatal formed the study population. Depression rate was measured using the original 1961 Beck’s Depression Inventory (BDI). In addition, a sociodemographic questionnaire (SDQ) was used to collect hypothesized risk variables. Multivariable logistic regression analysis was used to explore predictors of PND. Results The overall prevalence of PND in the sample of women was 27.1%. Women aged 18-24 (β = 2.04 95% C.I.[0.02; 4.05], p = 0.047), dissatisfied with body image (β = 4.33 95% C.I.[2.26; 6.41], p < 0.001), had an unplanned pregnancy (β = 2.31 95% C.I.[0.81; 3.80], p = 0.003 and felt fatigued (β = − 1.85 95% C.I.[− 3.50; 0.20], p = 0.028) had higher odds of developing PND. Participants who had no stressful life events had significantly lower depression scores as compared to those who had stressful life events (β = − 1.71 95% C.I.[− 3.30; − 0.11], p = 0.036) when depression was treated as a continuous outcome. Sensitivity analysis showed that mothers who had secondary and tertiary level of education had 51 and 73% had lower likelihood of having depression as compared to those with a primary level of education (A.O.R = 0.49 95% C.I.[0.31-0.78], p = 0.002) and (A.O.R = 0.27 95% C.I.[0.09-0.75], p = 0.013) respectively. Conclusion This study reveals key predictors/risk factors for PND in low-income settings building upon the scanty data. Identifying risk factors for PND may help in devising focused preventive and treatment strategies.